Nutritional protocols that alter ruminal fermentation and nutrient disappearance to increase marbling precursors in Nellore cattle - Squizatti, Mariana M. [UNESP]; Silvestre, Antonio M. [UNESP]; Felizari, Luana D. [UNESP]; Demartini, Breno L. [UNESP]; Silva, Leandro A.F. [UNESP]; Casali, Daniel M. [UNESP]; Miranda, Lidiane S. [UNESP]; Souza, Katia L.R. [UNESP]; Gasparini, Vanessa G. [UNESP]; Schleifer, Werner F. [UNESP]; Silva, Thaiano I.S. [UNESP]; Souza, Johnny M. [UNESP]; et al. (Elsevier, 2025)
The aim of this was to investigate the effects of various nutritional protocols on the marbling precursors of Nellore cattle, including high-moisture corn (HMC), calcium salts of fatty acids (CSFA) and organic zinc and chromium (ZnCr) in the finishing diet. Five Nellore steers fitted with ruminal cannulas were utilized in a 5 × 5 Latin square design, with each period lasting 28 days and a 7-day washout between periods. Animals were randomly allocated to one of five treatments in each period: T1) Finely-ground corn (FGC); T2) HMC; T3) FGC + CSFA T4) HMC + CSFA, and T5) HMC + CSFA + ZnCr. Sodium monensin was added to all treatments at a dosage of 25 ppm. The replacement of FGC with HMC reduced dry matter intake by 5.9 % (P = 0.02) and increased blood glucose concentrations by 24.6 % (P < 0.01) without significantly altering (P > 0.05) ruminal short-chain fatty acids (SCFA) and pH. The addition of CSFA decreased (P < 0.05) the ruminal degradability of nutrients such as dry matter, crude protein, and neutral and acid detergent fiber, without impacting propionate and SCFA concentrations in the rumen, as well as blood glucose and insulin levels (P > 0.05). An increase (P = 0.02) in protozoa populations from the genera Entodinium and Diplodinium was observed when CSFA were added to the diet. The addition of ZnCr increased the molar proportion of propionate (P = 0.01) from 29.29 to 38.08 mol/100 mol, resulting in a greater concentration of SCFA 12 h after feeding (P < 0.05). Moreover, adding ZnCr to the diet elevated insulin levels by 53.5 % and decreased blood glucose by 34.2 %. The addition of CSFA did not affect marbling precursors in Nellore cattle, and HMC only increased blood glucose concentrations. However, incorporating organic Zn and Cr into diets may enhance the positive effects of HMC and CSFA on marbling precursors.